2018
DOI: 10.1111/appy.12338
|View full text |Cite
|
Sign up to set email alerts
|

Psychological autopsy review on mental health crises and suicide among youth in Pakistan

Abstract: Introduction Ascertaining putative sociodemographic and clinical causes for death by probable suicide can potentially help implement region‐specific strategies to reduce suicide rates. In this study, we wanted to investigate methods utilized and the psychosocial and mental health characteristics of youths (aged 12‐26 y) who died by probable suicide. Method We examined data from mental health clinical files and forensic reports and performed qualitative psychological autopsy interview from more than multiple so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
(78 reference statements)
1
16
0
Order By: Relevance
“…[5][6][7][8] Mirroring global studies, the three most common methods for suicides in Pakistan are poisoning, firearms and hanging. 9,10 Pakistan Pakistan is the fifth most populous country in the world. 11 It is predominantly an agricultural country and, according to the 2017 National Census, around 64% of its population of 207 million is considered rural.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Mirroring global studies, the three most common methods for suicides in Pakistan are poisoning, firearms and hanging. 9,10 Pakistan Pakistan is the fifth most populous country in the world. 11 It is predominantly an agricultural country and, according to the 2017 National Census, around 64% of its population of 207 million is considered rural.…”
mentioning
confidence: 99%
“… 5 8 Mirroring global studies, the three most common methods for suicides in Pakistan are poisoning, firearms and hanging. 9 , 10 …”
mentioning
confidence: 99%
“…32 Overall, two studies were rated as high‐quality and 29 , 30 four as moderate‐quality 27 , 31 , 32 , 34 ; two others could not be assessed on six of the eight items due to the lack of a control group, and hence, the overall quality cannot be commented upon. 31 , 33 …”
Section: Resultsmentioning
confidence: 99%
“…The study also showed rates in men as 7.06 per 100,0000 and women as 3.08 per 100,000 in the Sindh province [8]. A recent psychological autopsy study from KP province identified major depression, use of harmful substances, lack of treatment compliance, financial issues, aggression, low self-confidence, family disputes and thoughts of self-harm as risk factors for suicide [9].…”
Section: Introductionmentioning
confidence: 85%
“…Over the last few years there have been anecdotal reports of increasing incidents of suicides, particularly of female suicides, in Gilgit-Baltistan (GB) in the Northern areas of Pakistan [10]. A study on female suicides in Ghizer district, GB showed crude rates as 14.89 per 100, 000 and an annual age-specific death rate for young females (15-24 years) as 61.07 per 100,000 for the years 2000 to 2004 [9]. An ethnographic study explored major factors associated with female suicides in GB and them as 1) Social factors including academic pressure, relationship problems, divorce and financial issues, 2) Cultural factors including lack of freedom, lack of decision making power and male child preference and 3) Psychological (mental illness and depression) [11].…”
Section: Introductionmentioning
confidence: 99%